Work Life Balance & Job Satisfaction: A Literature Review - Pathak, AK; Dubey, P; singh, Deepak (International Journal of Computer Sciences and Engineering, 2025)
The profitability and productivity of organization depends on the performance and commitment of its employees. Every employee has a personal and professional life; both of these are very difficult to separate. If an organization wishes to have better productivity and more commitment from employees then they have to be committed and satisfied. This can be achieved by an individual when have a fulfilled life inside and outside and his work and is accepted and respected for the mutual benefit of the individual and the organization. Organizations are social systems where human resources are the most important factors for effectiveness and efficiency and need effective managers and employees to achieve their objectives. Work life balance is partly employer’s and partly individual responsibility. The present article deals with surveying the past literatures on work life balance and job satisfaction in various sectors of Industries in India and abroad